Music in advertisement on social media platforms towards Malaysian young consumers’ decision making to purchase - Syazwani Mahsal Khan,; Norsiah Abdul Hamid,; Sabrina Mohd Rashid, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Advertising is a type of paid media in which people can promote their products and services through mainstream or social media platforms. It turns out to be progressively mainstream as more individuals who are dealing with their own businesses and organisations go to publicising as a stage to get their products or services known by their own consumers. The purpose of this study is to explore how information processing of music affects young consumers’ decision making in social media advertisements. The Elaboration Likelihood Model (ELM) is chosen as a framework to explore how information processed from music influences young consumer’s decision making process. The methodology utilised in this study was in-depth interviews with experts based on snowball sampling. The experts comprise of academicians, advertising professionals and musicians. Semi-structured interview questions were applied in this study. Then, thematic analysis uncovers two emerging themes: consumers’ preferences of products and consumers’ motivation on spending. The findings of this study revealed that information processed from music on advertisements, available on social media platforms, can affect young consumer’s decision making to purchase. This study contributed to our understanding that music used in an advertisement, and in this case on social media, can influence young consumers to develop preference towards the advertised product. This is a subtle approach to influence their decision to purchase products in the future. As a result, they are more likely to engage with upcoming product advertisements.